2016
DOI: 10.3109/13880209.2015.1137952
|View full text |Cite
|
Sign up to set email alerts
|

Possible effects ofPhillyrea latifoliaon weight loss in rats fed a high-energy diet

Abstract: Context Phillyrea latifolia L. (Oleaceae), commonly found in the Mediterranean region in Turkey, is used as medicinal teas for weight loss and hyperglycaemia in folk medicine. Objective The study investigated the possible effects of P. latifolia leaves aqueous extract's on weight loss and biochemical-histological changes in the rats fed a high-energy diet (HED), also isolated and determined the main phenolic compounds. Materials and methods Twenty-four male Wistar albino rats were divided into four equal group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Weight is of great concern nowadays. Overweight is associated with obesity, which is a risk factor of many deadly diseases such as diabetes, cancer, hypertension, liver disease, cardiovascular disease and cancer (Yazici-Tutunis et al, 2016). Moreover, present study revealed lack of significant histological lesions in the livers of the tamsulosin and carvedilol-administered rats, indicating that the two (2) drugs are not hepatotoxic.…”
Section: Histopathology Analysis Of and Livers At 6 Th And 8 Th Weekssupporting
confidence: 45%
See 1 more Smart Citation
“…Weight is of great concern nowadays. Overweight is associated with obesity, which is a risk factor of many deadly diseases such as diabetes, cancer, hypertension, liver disease, cardiovascular disease and cancer (Yazici-Tutunis et al, 2016). Moreover, present study revealed lack of significant histological lesions in the livers of the tamsulosin and carvedilol-administered rats, indicating that the two (2) drugs are not hepatotoxic.…”
Section: Histopathology Analysis Of and Livers At 6 Th And 8 Th Weekssupporting
confidence: 45%
“…This was similar to the past studies which showed that alpha-1 adrenoceptors blockers have an advantageous effect on total cholesterol and triglycerides (Kabra, 2014). This observation might suggest that this drug have normal effect on leptic (a hormone that contribute hugely in weight regulation), dopamine, and serotonin (Yazici-Tutunis et al, 2016). Other researchers have proposed mechanisms via which alpha-1 adrenoceptorblockers affect cholesterol and triglyceride synthesis which include up-regulation of low-density lipoprotein receptors, leading to suppression of 3-hydroxy-3-methyl-glutarylcoenzyme A reductase (HMG) activity and consequently leading to a reduction in total cholesterol and low-density lipoprotein (Katzung, 2009).…”
Section: Histopathology Analysis Of and Livers At 6 Th And 8 Th Weeksmentioning
confidence: 97%
“…These compounds receive special attention nowadays for their biological activities, such as antimicrobial, anti-inflammatory, and anticancer [9,12]. Given the high flavonoid content of the studied species (Figure 2), they would represent raw materials for potential different products, including pharmaceutics and nutraceuticals that are based both on their traditional uses [23][24][25][26] and the scientific evidence [28,29,37,39].…”
Section: General Phenolic Profile Of the Leaf Extractsmentioning
confidence: 99%
“…Together, these compounds summed more than 90% of TPC (Figure 2A). Flavonoids with quercetin and luteolin aglycones were already described as important constituents of P. latifolia leaves [23,34,39,40]. Both aglycones have a catechol group in B ring of the flavonoid structure, a feature that confers them a high potential as free-radical scavengers [45].…”
Section: General Phenolic Profile Of the Leaf Extractsmentioning
confidence: 99%
See 1 more Smart Citation